2019
DOI: 10.1177/1941738119827966
|View full text |Cite
|
Sign up to set email alerts
|

Head Trauma Exposure in Mixed Martial Arts Varies According to Sex and Weight Class

Abstract: Mixed martial arts" (MMA) is an umbrella term for a combat sport that encompasses athletes with backgrounds in several fighting disciplines that mainly involve standing strikes, grappling, and locking techniques. 9,11 Despite the increasing popularity of MMA worldwide, numerous medical associations around the globe have called for the banishment of the sport, mainly based on presumed risk of brain injury. 7,11,12 In response, a cooperative work at different levels has been developing to diagnose, recognize, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…19 Both male and female MMA fighters in heavier weight classes have been found to have elevated risk for sustaining knock-outs and technical knock-outs from strikes to the head. 42 The finding of yearly decline in regional brain volume and cognition among heavyweight and middleweight fighters suggests that the force of individual strikes may influence post-TBI functional outcomes independently from the total number of strikes sustained during professional bouts. However, as the interaction effects suggest, this relationship is complex.…”
Section: Discussionmentioning
confidence: 99%
“…19 Both male and female MMA fighters in heavier weight classes have been found to have elevated risk for sustaining knock-outs and technical knock-outs from strikes to the head. 42 The finding of yearly decline in regional brain volume and cognition among heavyweight and middleweight fighters suggests that the force of individual strikes may influence post-TBI functional outcomes independently from the total number of strikes sustained during professional bouts. However, as the interaction effects suggest, this relationship is complex.…”
Section: Discussionmentioning
confidence: 99%
“…MMA fighters were significantly more likely to experience injury (typically contusion/bruising) compared to boxers [ 27 ]. Because blows directly to the head are an effective way to achieve a win, MMA has reported even higher rates of traumatic brain injury than those assessed in American-style football, ice hockey or other contact sports [ 28 , 29 ], and the injury incidence in MMA appears to be greater than in most, if not all, other popular and commonly practiced combat sports [ 23 ]. In contrast to these findings, Curran-Sills and Abedin [ 30 ] reported that MMA does not confer the same exposure to concussion over a 10-year period as seen in other popular sports (e.g., ice hockey, American football, rugby union), but it is important to avoid this simplified derivation because of methodological differences across the studies [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain injury arising from head trauma is a major concern in MMA because knockout (KO) or technical knockout (TKO) are frequent fight outcomes, many movement combinations are targeted to hit the head area [36], and previous studies have shown a high incidence of matches ending due to strikes to the head. Strikes to the head are the major techniques used to end a match via KO/TKO, regardless of sex and weight class [28]. Based on an examination of 440 matches from 2002 to 2014, the main cause of injuries in doctor-stoppage situations was facial injuries (90%), with 87.1% occurring after striking actions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not look at the effect of fighter weights on rate of ophthalmic injury, which is a factor that has been identified as associated with overall injury rates in previous studies. 24 , 25 Our inclusion of whether or not a fighter was injured was limited to the report of the physician at ringside, as we did not review individual fight videos to confirm injuries or mechanism of injury. We also did not include information on age or the round when the injury was sustained, which are factors that were identified with overall injury in previous studies.…”
Section: Discussionmentioning
confidence: 99%